Dermatology Clinical Case Modules: 40-Year-Old Woman With a Dark Mole - Lisa Nguyen; Meera Mahalingam; Amit Garg (Association of American Medical Colleges, 2010)
Abstract This web-based clinical case module is part of a series of online modules being developed for the medical student curriculum in dermatology. This self-directed resource serves as a supplement to traditional lecture and clinical teaching. The purpose of this module is to help students develop a clinical approach to the evaluation and initial management of patients presenting with suspicious pigmented lesions that are concerning for malignant melanoma. In this case, a 40-year-old woman presents with a dark, suspicious mole. As users navigate through the module, they are presented with various decision branch points in the care of the patient. In this way, the module seeks to closely mimic a true clinical experience as students are able to see the consequences of their clinical decision-making. Users also learn how to appropriately counsel the patient on healthy sun protection habits and preventative skin surveillance. A comprehensive summary of key points on melanoma (including epidemiology, etiology, treatment, and prognosis) may be reviewed at the end of the module. The module requires PowerPoint 2007 or Microsoft Office 2007 compatibility. Computer-assisted instruction has been shown to be at least as effective as traditional lecture in teaching dermatology morphology to medical students. The effectiveness and significance of the present work are under study. We plan to use pre- and postassessments to evaluate the effectiveness of this module.